The development of the Australian Unemployed Workers Union Rating Scale (AUWURS) of employment service providers. Issue 4 (24th February 2022) - O'Halloran, David; Farnworth, Louise; Thomacos, Nikos
Abstract: This article reports on the ongoing development of the Australian Unemployed Workers Union Rating Scale (AUWURS), which allows unemployed workers to rate their experiences of employment services to allow the evaluation and improvement of service delivery, as well as an aid to the selection of a service provider. The seven subscales comprising the AUWURS ('Useful', 'Client Centred', 'Fair', 'Trustworthy', 'Responsive to Feedback', 'Friendly', and 'Realistic') reflect the multifaceted nature of unemployed workers' experiences of employment services and it offers a way for employment services to be held accountable to a significant stakeholder group whom they aim to serve—unemployed workers. Abstract : The Australian Unemployed Workers Union Rating Scale (AUWURS) allows unemployed workers to rate their experiences of employment services according to seven criteria: Useful, Client Centred, Fair, Trustworthy, Responsive to Feedback, Friendly, and Realistic and means employment services can be held accountable to those they aim to serve – unemployed workers.